Indonesia-Finland Renewable Energy Development Cooperation - Aos Yuli Firdaus; Harun Umar (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2022)
As the largest archipelagic country globally, Indonesia requires much energy to develop and preserve development and its natural wealth. As a biologically rich country, Indonesia has eight (8) renewable energy sources that must be processed and then utilised for maximum energy fulfilment throughout the archipelago and must be adjusted to its geographical specifications. The declaration of cooperation between Indonesia and Finland was signed by diversifying renewable energy sources from solar energy, bioenergy, and ocean wave energy. The implementation based on the MoU is the first to develop practical and environmentally sound technology using wind energy and ocean wave energy. The application of ocean wave energy as an alternative source of electrical energy by using technology. Second, the development of natural resources and technology in the electricity sector. This condition is done by building a micro hydropower plant. This research shows that cooperation between the two countries is quite effective. Both countries depend on each other to fulfil their respective interests. Because of that, there has been an effect between countries to re-enhance cooperation in the energy sector for a relatively long period, starting again from 2011–to 2014.